The Anatomy of Banking Crises - Duttagupta, Rupa (IMF Working Papers; Working Paper ;, 2008)
This paper uses a Binary Classification Tree (BCT) model to analyze banking crises in 50 emerging market and developing countries during 1990-2005. The BCT identifies key indicators and their threshold values at which vulnerability to banking crisis increases. The three conditions identified as crisis-prone-(i) very high inflation, (ii) highly dollarized bank deposits combined with nominal depreciation or low liquidity, and (iii) low bank profitability-highlight that foreign currency risk, poor financial soundness, and macroeconomic instability are key vulnerabilities triggering banking crises. The main results survive under alternative robustness checks, confirming the importance of the BCT approach for monitoring banking system vulnerabilities.